Allelopathic potential and competitive traits of sweetpotato cultivars - Werle, Isabel S.; Noguera, Matheus M.; Karaikal, Srikanth K.; Carvalho-Moore, Pamela; Kouame, Koffi Badou-Jeremie; Tseng, Te-Ming; Roma-Burgos, Nilda (Frontiers in Agronomy, 2022)
Allelopathy and competition are components of plant-plant interactions, delimiting the level of interference. Understanding this interaction has practical applications in agriculture. Crop cultivars possessing high allelopathic ability and competitive traits are themselves tools for sustainable weed management, enabling reduced use of herbicides. Greenhouse and field experiments were conducted to assess the weed suppressive ability of selected sweetpotato (Ipomoea batatas L.) cultivars. The effect of nine cultivars on Palmer amaranth (Amaranthus palmeri S. Watson), junglerice (Echinochloa colona L.), and hemp sesbania (Sesbania hederacea P. Mill.) was first evaluated in the greenhouse. The experiment was set up in a completely randomized design with four replications and conducted twice. Sweetpotatoes were cultured in sand. The target weeds were seeded in pots filled with a 2:1 mix of field soil:potting mix and watered with 100-ml aliquot of sweetpotato root leachates once every 2 d. Weed height and shoot biomass were measured. ‘Heartogold’, ‘Centennial’, and ‘Stokes Purple’ were the most allelopathic cultivars. Junglerice was most inhibited by sweetpotato leachates. Nine cultivars were evaluated in the field. Experiments were conducted at Fayetteville and Kibler, Arkansas, USA, in a split-plot design, with weed infestation (broadleaf spp., grass spp., or weed-free) as whole plot and the cultivars as split-plot. Across locations, ‘Beauregard-14’ had the longest vines, whereas ‘Hatteras’ and ‘Heartogold’ had the tallest canopy. ‘Heartogold’ had the largest leaf area. This cultivar reduced weed biomass 2- to 4-fold in both locations. Yield was reduced on average 55 and 68% with grass and broadleaf weeds across locations, respectively. ‘Beauregard-14’ and ‘Bayou Belle-6’were the high-yielding cultivars in Kibler and Fayetteville. The highest yielding cultivars were not the most weed suppressive but did not incur the highest yield loss from weed competition, indicating the ability to withstand weed interference. Cultivar competitiveness, weed-suppressive ability, and weed tolerance are important factors that should be considered before making a cultivar selection.